PERAN METODE PRAKTIKUM DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM DI MADRASAH IBTIDAIYAH STUDI DESKRIPTIF KEAKTIFAN DAN HASIL BELAJAR SISWA - Syaifudin Syaifudin (Mentari : Journal of Islamic Primary School, 2023)
One effective method of teaching science is through experiments/practicals, which can be conducted using simple tools and materials that are easily found around us. The purpose of this research is to determine the activity and learning outcomes of fifth-grade students at Madrasah Ibtidaiyah Negeri 4 Lampung Selatan in the topic of heat transfer using the practical method that utilizes tools and materials that are easily found in the surrounding environment. This research is included in the Pre-Experimental Design research with One-Shot Case Study design. The population in this research is all fifth-grade students of MIN 4 Lampung Selatan in the academic year 2022/2023, with a total of 30 students all of whom are used as research samples. The research instruments used are observation sheets for student learning activity and test questions in the form of essay questions. The data analysis technique used is descriptive statistical data analysis. The results of the research and data analysis show that the category of student learning activity is very high at 77% and high at 23%, while for student learning outcomes that reach the Minimum Mastery Criteria (KKM) is 83% and those who have not reached KKM is 17% with an average score of 82.83. The results of the research indicate that the activity and learning outcomes of students in science learning using the practical method are very high.